2011
DOI: 10.4236/eng.2011.31011
|View full text |Cite
|
Sign up to set email alerts
|

A QoE Assessment System in Distance Education

Abstract: It is a challenging task to improve the real-time property and objectivity of the effect assessment for the distance education. This paper presents a QoE (Quality of Experience) assessment system based on the attention of online user. The system captures the video frames from two cameras periodically and synchronously, using the adaptive image binarization based on the linear average threshold for the pretreatment, then processing with edge detection and filtering in the cross-directions at the same time. Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It indicates the degree to which the service meets user anticipation, especially from the user's point of view to the valuation performance of the service, Figure-1 show that QoE is an extension to the QoS. The evolving in the network infrastructure and e-commerce environment making the Service providers concern great weight to quality control and are associated with improving the quality of the user experience as one of the main competition methods [5].…”
Section: Ghani and Ajrashmentioning
confidence: 99%
See 2 more Smart Citations
“…It indicates the degree to which the service meets user anticipation, especially from the user's point of view to the valuation performance of the service, Figure-1 show that QoE is an extension to the QoS. The evolving in the network infrastructure and e-commerce environment making the Service providers concern great weight to quality control and are associated with improving the quality of the user experience as one of the main competition methods [5].…”
Section: Ghani and Ajrashmentioning
confidence: 99%
“…The quality of service (QoS) define the overall characteristics of a service such as communication that affect the satisfied of user's service needs [5].From video streaming point, QoS indicated to the capability of the network to transmit packet in the best way possible, QoS represents the networkcentric. However, the obvious question is how QoS control and measure the perception of user's service.…”
Section: The Difference Between Qos and Qoementioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, QoE ("Quality of Experience", 2011) has emerged as a fully user-oriented approach which focuses on the social element, users' subjective expectation and evaluation of systems' delivery and performance (Kalliris, Dimoulas, Veglis, & Matsiola, 2011;Kist & Brodie, 2012;W. Wu et al, 2009;Zhang, Xu, & Cheng, 2011). Furthermore, videoconferencing-based educational systems provide tremendous convenience and flexibility for adult students, while bridging the distance between the teacher as a source of information and the students.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…In the same context, different studies have already demonstrated QoE as a more holistic evaluation than mere narrowly focused end-user experience (Kalliris et al 2011;Molnar, Hava-Muntean, & Cristea, 2009;W. Wu et al, 2009;Zhang et al, 2011). Gong, Yang, Huang and Su (2009) have defined a QoE model that focused on the relationship between the technical and QoE parameters that consisted of five factors: availability, usability, integrality, retainability and instantaneousness.…”
Section: Literature Reviewmentioning
confidence: 99%